Orientation Holding Control for Autonomous Surface Vehicles using Adaptive Neuro-Fuzzy Inference System Method - Dimas Prostovani Riananda; Nurahmad Hadi Cahyadi; Zindhu Maulana Ahmad Putra; Joko Endrasmono; Ryan Yudha Adhitya; Agus Khumaidi (International Conference on Maritime Technology and Its Application, 2025)
The completion of autonomous surface vehicle water missions is required to have adaptive capabilities in maintaining the position, attitude or tilt, and stability of the ship against the influence of external disturbances that can interfere with the ASV's navigation system. Therefore, this research focuses on the orientation holding control system against external disturbances. To determine the value of the angular shift or tilt of the ship's facing direction using the CMPS14 sensor. The control method used to determine the ship's propulsion response in determining the speed based on the heading error value and the amount of rotation speed through the bow thruster in maintaining the ship's heading using the ANFIS (Adaptive Neuro-Fuzzy Inference System) Method. The ANFIS model that has been made for predicting the value has an RMSE value of 1.6169% which is then implemented on a microcontroller with conversion and has an accuracy value of 99,6%. In testing the performance of the ship orientation control system by giving 10 variations of disturbance shows an average response time of 5.08 seconds. So that the application of the ANFIS method in this control system has good performance and can be used as a reference for further research.